Implementasi Agile Project Management Pada Pengembangan Perangkat Lunak - Rifqi Taufiqurrohman; Muhammad Nur Rahman; Arianda Budiman; Andri Rosandi; Ignasius Riandro Raul; Agung Wijoyo (CV. Multi Kreasi Media, 2024)
Today's software development is increasingly complex and requires development teams to use the right development methodology so that software development projects can be successful. One of the increasingly popular methodologies is Agile Project Management. Agile Project Management is a software development methodology that is adaptive, flexible and encourages collaboration between development teams and stakeholders in achieving project goals. This article discusses the application of Agile Project Management in software development. We start by explaining the basic concepts of Agile Project Management, such as the Agile development life cycle, basic principles, and Agile framework. Next, we describe the steps required to implement Agile Project Management in software development, including team building, planning, execution, testing, and evaluation.